ENGLISH LEARNING MODEL AT 'TA'MIRUL ISLAM' BOARDING HOUSE OF SURAKARTA (MODEL PEMBELAJARAN BAHASA INGGRIS DI PONPES 'TA'MIRUL ISLAM' SURAKARTA) - Faizal Risdianto (UIN Raden Mas Said Surakarta, 2016)
This research applies descriptive qualitative method aiming at knowing the format and model as well as the motivating and resisting power of English learning at Ta’mirul Islam Male Boarding School Surakarta. From observations and interviews, it is found that there is as direct learning strategy using teacher-centered approach. This learning strategy is even more detailed by the ‘army method’ learning model which emphasizes high discipline and teacher authority as well as direct method which stresses on the teacher instructions. The learning model of the school follows behavioristic patterns that emphasizes on customization in language skills. It is combined with army method patterns that treat students with rewards and punishments. The motivating power of the English learning process at the boarding house is the availability of facilities, bi’ah lughowiyah or the environment that supports the students to be able to speak and write in English. Meanwhile, the ressisting factor is the ignorance of most students toward the punishments given by the authority.